Water Crisis Management in Rainfed Agriculture – The Context of Flash Flood and Drought in Thailand - Patsinghasanee, Supapap; Laonamsai, Jeerapong; Sawanyapanich, Punyawee (Engineering and Technology Horizons, 2022)
In the context of water crisis management, the urgent need for water resources management in agriculture and disaster management to meet future food and livelihood needs is highlighted, especially given the pressure and stress on water management and the uncertainty caused by climate variability. Rainfed agriculture in Thailand’s rural areas plays and will remain an important role in providing food, generating livelihoods, and ensuring water security. The primary aims of the project are to forecast and evaluate the flash flood guidance system and the seasonal drought forecasting system. The case study for real-time hydrological forecasting of flash flood risk is during the tropical storm "SINLAKU" on August 2–5, 2020. For the seasonal drought forecasting system, the water balance process has been used to determine water deficit areas at the sub-district level in the dry season from 2019 to 2020. Furthermore, disaster management is being used to establish the water crisis prevention and mitigation plan prior to, during, and after a disaster. As a result, water crisis prevention and mitigation procedures have been implemented in rainfed agriculture to reduce the severity of disasters.